Analisis Literasi Halal, Label Halal, Islamic Branding, dan Religious Commitment pada Pembelian Makanan di Tsabita Halal Bakery - Hayati, Safaah Restuning; Putri, Syah Amelia Manggala (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The food and beverage industry has the largest market share in the world. In Muslim countries, this industry contributes 16.6% of the total global food and beverage industry. The size of this industry in general also reflects the large potential of halal food and beverages. In Indonesia, the very high growth in consumption of halal food is driven by various factors, such as the desire of Muslim consumers to consume food ingredients in a halal and good manner (thayyib) according to religious orders. This study aims to determine the effect of halal literacy, halal labeling, Islamic branding, and religious commitment on the decision to purchase halal food at Tsabita Halal Bakery. This research is a descriptive quantitative type. This study uses data analysis techniques Structural Equation Modeling (SEM) or structural equation model. Sampling using simple random sampling. The results of this study indicate that halal literacy and halal labels have a contribution in encouraging consumers to buy halal food at Tsabita Halal Bakery. While Islamic branding and religious commitment have no influence on the purchase of halal food at Tsabita Halal Bakery. For this reason, Tsabita needs to strengthen her Islamic branding and continue with Islamic marketing through social media, considering that the millennial generation is very social media literate. Religious commitment also has no effect on purchases, it can be caused by the low level of respondents' religiosity.